Effect of using portland cement and tras soil to stabilize and solidify mercury-contaminated tailings in small-scale gold mining. Issue 1 (October 2021) - Rachman, R M; Ngii, E; Sriyani, R
Abstract: Small scale gold mining in Kulon progo district using mercury for binding gold. The total concentration of mercury in tailings has 383.21 mg/kg. Stabilization/solidification is one of the remediation technologies to reduce waste pollution. This research aims to know the optimum composition in the S/S process. The first stage uses a composition between Portland cement: tras soil. the ratio are 100: 0, 90:10, 80:20, 70:30, 60:40, 50:50, 40:60., 30:70, 20:80, and 10:90. In the second stage, the tailings sample is added to the optimum from the first stage, with the composition of the binder: tailings. the ratio are 50:50, 40:60, 30:70, 20:80, and 10:90. The TCLP is applied according to the US EPA 1311 method. The first test results in the optimum composition of Portland cement: tras soil (10:90), the compressive strength test value of 96 kg/cm 2 . The compressive test result met the quality standards of The Head of Environmental Impact Control Agency (BAPEDAL) Decree KEP-03/BAPEDAL/09/1995 for the management of contaminated soil at 1 kg/cm 2 . The second test of binding: tailings (50:50) was 39.2 kg/cm 2 with no detectable mercury concentration. TCLP test results meet the S/S product quality based on Government Regulation 101 of 2014 of 0.05 mg/L.